Bicaudal-D uses a parallel, homodimeric coiled coil with heterotypic registry to coordinate recruitment of cargos to dynein - Liu, Yang (Cold Spring Harbor Laboratory Press, 2013)
Cytoplasmic dynein is the major minus end-directed microtubule motor in eukaryotes. However, there is little structural insight into how different cargos are recognized and linked to the motor complex. Here we describe the 2.2 Å resolution crystal structure of a cargo-binding region of the dynein adaptor Bicaudal-D (BicD), which reveals a parallel coiled-coil homodimer. We identify a shared binding site for two cargo-associated proteins—Rab6 and the RNA-binding protein Egalitarian (Egl)—within a region of the BicD structure with classical, homotypic core packing. Structure-based mutagenesis in Drosophila provides evidence that occupancy of this site drives association of BicD with dynein, thereby coupling motor recruitment to cargo availability. The structure also contains a region in which, remarkably, the same residues in the polypeptide sequence have different heptad registry in each chain. In vitro and in vivo analysis of a classical Drosophila dominant mutation reveals that this heterotypic region regulates the recruitment of dynein to BicD. Our results support a model in which the heterotypic segment is part of a molecular switch that promotes release of BicD autoinhibition following cargo binding to the neighboring, homotypic coiled-coil region. Overall, our data reveal a pivotal role of a highly asymmetric coiled-coil domain in coordinating the assembly of cargo–motor complexes.